Experimental investigation on vortex-induced force of a Steel Catenary Riser under in-plane vessel motion. (July 2021) - Zhang, Mengmeng; Fu, Shixiao; Liu, Chang; Ren, Haojie; Xu, Yuwang
Abstract: A method to identify vortex-induced forces and coefficients from measured strains of a Steel Catenary Riser (SCR) undergoing vessel motion-induced Vortex-induced Vibration (VIV) is proposed. Euler–Bernoulli beam vibration equations with time-varying tension is adopted to describe the out-of-plane VIV responses. Vortex-induced forces are reconstructed via inverse analysis method, and the Forgetting Factor Least Squares (FF-LS) method is employed to identify time-varying vortex-induced force coefficients, including excitation coefficients and added mass coefficients. The method is verified via a finite element analysis procedure in commercial software Orcaflex. The time-varying excitation coefficients and added mass coefficients of an SCR undergoing vessel motion-induced VIV are investigated. Results show that vessel motion-induced VIV is excited at the middle or lower part of the SCR and in the acceleration period of in-plane velocity, where most of the excitation coefficients are positive, while during the deceleration period, the excitation coefficients becomes too small to excite VIVs. Parameter γ [1] has strong correlation with excitation coefficients. In addition, time-varying tensions contribute significantly to the variations of added mass coefficients under the condition that the ratio of dynamic top tension to pretension exceeds the range of 0.7–1.3. Moreover, chaotic behaviors are observed in vortex-induced force coefficients and are more evident with the increase of vessel motion velocity. This behavior may attribute to the randomness existing in in-plane velocity and its coupling with out-of-plane vibrations. Highlights: A method to identify vortex-induced force coefficients from measured strains of a Steel Catenary Riser (SCR) undergoing vessel motion-induced VIV is proposed. In acceleration period of in-plane velocity, VIVs excite at the middle part of the SCR where excitation coefficients are positive and KC numbers are maximum. In deceleration period of vessel motion, the excitation coefficient gets too small to excite a significant VIV. There exists an approximately linear relationship between dynamic tension ratio Tn and added mass coefficients under the condition of Tn exceeding the range of 0.7–1.3. Chaotic behaviors are observed in the VIF coefficients and are more evident with the increase of vessel motion velocity.